HEKİMİN AYDINLATMA YÜKÜMLÜLÜĞÜ - (:unkn) unknown (My University, 2018)
Hekimin uyguladığı tıbbi müdahalenin hukuka uygun olması içinhekimin hastayı aydınlatma yükümlülüğü bulunmaktadır. Aydınlatmayükümlülüğünün yerine getirilmesi ile hasta ile hekim arasında güvenilişkisi tesis edilir ve hasta vücut bütünlüğünü korur. Aynı zamanda has-tanın özerkliğinin sağlanabilmesi için hekimin aydınlatma yükümlülü-ğünü yerine getirmesi önemli rol oynar. Bu çalışma ile söz konusu yü-kümlülüğün hukuki dayanakları, kapsamı, unsurları ve sınırları Türk,Alman ve Anglo-Amerikan öğretisi ve yargı kararları ışığında incelenmiştir.

A practitioner has liability for informing patients in order for the medical practice the practitioner applies to be legal. Informing patients before getting consent for the medical practice sets confidence between the practitioner and patients and protects physical integrity of the latter Fulfilment of informing liability also plays a crucial role in assuring patients’ autonomy in practitioner-patient relations. This article exami- nes the legal grounds, scope, conditions and limits of informing liability in the light of Turkish, German and Anglo-American doctrine and jud- gements.
OBLIGATION OF PHYSICIANS TO INFORMED CONSENT
Keywords: Hukuk